The Comparative Impact of Integrated Assessment Models' Structures on Optimal Mitigation Policies - Baptiste Perrissin Fabert; Etienne Espagne; Antonin Pottier; Patrice Dumas (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper aims at providing a consistent framework to appraise alternative modeling choices that have driven the so-called when flexibility" controversy since the early 1990s dealing with the optimal timing of mitigation efforts and the Social Cost of Carbon (SCC). The literature has emphasized the critical impact of modeling structures on the optimal climate policy. But, to our knowledge, there has been no contribution trying to estimate the comparative impact of modeling structures within a unified framework. In this paper, we use the Integrated Assessment Model (IAM) RESPONSE to bridge this gap and investigate the structural modeling drivers of differences in climate policy recommendations. RESPONSE is both sufficiently compact to be easily tractable and detailed enough to capture a wide array of modeling choices. Here, we restrict the analysis to the following emblematic modeling choices: the forms of the damage function (quadratic vs. sigmoid) and the abatement cost (with or without inertia), the treatment of uncertainty, and the decision framework (one-shot vs. sequential). We define an original methodology based on an equivalence criterion to carry out a sensitivity analysis over modeling structures in order to estimate their relative impact on two output variables: the optimal SCC and abatement trajectories. This allows us to exhibit three key findings: (i) IAMs with a quadratic damage function are insensitive to changes of other features of the modeling structure, (ii) IAMs involving a non-convex damage function entail contrasting climate strategies, (iii) Precautionary behaviours can only come up in IAMs with non-convexities in damages.
Keywords: Q5; Q58; 330; Integrated Assessment Models; Mitigation